2001
DOI: 10.1093/embo-reports/kve069
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination in planta is stimulated in the absence of Rad50

Abstract: Chromosomal double-strand DNA breaks must be repaired; in the absence of repair the resulting acentromeric (and telomereless) fragments may be lost and/or the broken DNA ends may recombine causing general chromosomal instability. The Rad50/Mre11/Xrs2 protein complex acts at DNA ends and is implicated in both homologous and non-homologous recombination. We have isolated a rad50 mutant of the plant Arabidopsis thaliana and show here that it has a somatic hyper-recombination phenotype in planta. This finding supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 31 publications
2
103
1
Order By: Relevance
“…Rad51C deficiency also results in reduced frequencies of somatic recombination in Rad51C knockout DT40 and CL-V4B cells Drexler et al, 2004). To determine the direct involvement of AtRad51C in HR, we measured the frequencies of somatic recombination in the atrad51C mutant with GUS recombination reporter system developed by the group of B. Hohn (Swoboda et al, 1994;Gherbi et al, 2001). Using this system, we confirmed that AtRad51C required the efficient recombination in somatic cells (Table I; Fig.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Rad51C deficiency also results in reduced frequencies of somatic recombination in Rad51C knockout DT40 and CL-V4B cells Drexler et al, 2004). To determine the direct involvement of AtRad51C in HR, we measured the frequencies of somatic recombination in the atrad51C mutant with GUS recombination reporter system developed by the group of B. Hohn (Swoboda et al, 1994;Gherbi et al, 2001). Using this system, we confirmed that AtRad51C required the efficient recombination in somatic cells (Table I; Fig.…”
Section: Discussionmentioning
confidence: 72%
“…We used both direct-and inverted-repeat recombination reporter lines (1406 and 1415) for the evaluation of somatic HRF in the atrad51C mutant. In the case of the direct repeat, the production of a functional recombined GUS gene occurs by gene conversion/crossover or single-strand annealing mechanisms; on the other hand, only a gene conversion/crossover produced a functional recombined GUS gene for the inverted repeat (Gherbi et al, 2001;Dubest et al, 2004). Somatic HRF in atrad51C reduced in both direct-and invertedrepeat reporter lines at similar rates under or without genotoxic stresses (Table I).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The articles reporting the use of this line cite one or more of the following sources: Tinland et al (1994), Gherbi et al (2001), Fritsch et al (2004), or Lucht et al (2002, yet none of these cited articles offers any detailed information on this line. Therefore, the origin of this line is unclear, along with the details of transgene copy number and location.…”
Section: Poorly Characterized Shr Line 1445mentioning
confidence: 99%